High‐Efficiency, Solution‐Processed, Multilayer Phosphorescent Organic Light‐Emitting Diodes with a Copper Thiocyanate Hole‐Injection/Hole‐Transport Layer. (10th November 2014) - Perumal, Ajay; Faber, Hendrik; Yaacobi‐Gross, Nir; Pattanasattayavong, Pichaya; Burgess, Claire; Jha, Shrawan; McLachlan, Martyn A.; Stavrinou, Paul N.; Anthopoulos, Thomas D.; Bradley, Donal D. C.
<x xml:space="preserve">Abstract</x> Copper thiocyanate (CuSCN) is introduced as a hole‐injection/hole‐transport layer (HIL/HTL) for solution‐processed organic light‐emitting diodes (OLEDs). The OLED devices reported here with CuSCN as HIL/HTL perform significantly better than equivalent devices fabricated with a PEDOT:PSS HIL/HTL, and solution‐processed, phosphorescent, small‐molecule, green OLEDs with maximum luminance ≥10 000 cd m‐2, maximum luminous efficiency ≤50 cd A‐1, and maximum luminous power efficiency ≤55 lm W‐1 are demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>